The Reality of The Training Programs Introduced to The Principals of Private Schools in The Province of North Batinah In the Sultanate of Oman - Al-Zadjali, Ahmed Khamis Mahmood (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to identify the reality of the training programs of private school principals in the province of North Batinah in the Sultanate of Oman and to know the significance of the differences in the effectiveness of the training programs provided to the principals of private schools in the province of North Batinah in the Sultanate of Oman, depending on the variables of gender, Years of administrative experience), the researcher selected 26 managers from private schools in the North Al Batinah Governorate in the Sultanate of Oman. After searching for information it became clear that (3) schools with principals are charged by the schools and have no data at the Directorate. Thus, the study sample consisted of (23) managers To analyze the results of the study, the arithmetic mean and standard deviations were extracted, the T test was used for the independent samples, and the ANOVA test was used to analyze the mono-variance. The most important findings of the study: • There is effectiveness of the training programs provided to the principals of private schools in the province of North Batinah in the Sultanate of Oman. • There were statistically significant differences at a level of significance less than (0.05) due to the gender variable in the dimension (training environment) and in favor of males compared to females and the absence of differences in the other dimensions of the study instrument • There were no statistically significant differences at a level of significance less than 0.05 among the study sample members in the dimensions of the study instrument according to the variable of the scientific qualification. • There are statistically significant differences at a level of significance less than 0.05 among the study sample members in the objectives of the training program and for their experience of 5-10 years. There are no statistically significant differences in the other dimensions according to the variable years of experience. The study concluded with a number of recommendations, the most important of which are: • Utilize managers’ views on the evaluation aspects of training programs that feel that they need to further evaluate their training programs to achieve a higher level of productivity. • Clear criteria should be adopted for selecting staff to participate in training courses